Keberlanjutan Ekologi dan Strategi Pemanfaatan Sumberdaya Perikanan: Mewujudkan Maluku Sebagai Lumbung Ikan Nasional - Suhaemi, Suhaemi; Angkotasan, Abdul Motalib; Tawari, Ruslan Husen Saban; Daud, Asmar Hi; Norau, Sahlan; Sangadji, Muhamad Siddiq; Sangadji, Selfi (Jurnal Sumberdaya Akuatik Indopasifik, 2025)
Selected as the National Fish Reserve (LIN), Maluku Province is known for its abundant marine resources and enormous fishery potential, supported by a capture fishery area of 658,294.69 km² which is the largest in Indonesia. Maluku has three Fishery Management Areas of the Republic of Indonesia (WPPNRI), namely WPPNRI-714, WPPNRI-715, and WPPNRI-718. However, based on production data for the capture fishery and aquaculture sectors in Maluku Province during the 2018-2022 period, these resource potentials have not been optimally utilized. Therefore, this research aims to analyze the ecological conditions and utilization of fishery resources in Maluku Province as a consideration for developing targeted policies and strategies for fishery resource utilization. This research uses a quantitative descriptive approach with data presented in narrative format, simple tables, graphs, and Multidimensional Scaling (MDS) analysis. Data collection was conducted from various sources over a 5-year period (2018-2022). Based on the analysis results, the status of ecological conditions and fishery resource utilization in Maluku Province is classified as less sustainable, indicated by Rapfish scores below 50. To improve the sustainability of fishery resource management in this region, strengthening of monitoring systems and community education about the importance of aquatic ecosystem conservation is needed.